Los orígenes del cuento moderno peruano en las revistas ilustradas de inicios del siglo xx. El caso de María Augusta Arana - Velázquez, Marcel (2024)
The production, circulation and consumption of the first modern short stories, by foreign and national authors, occurred in illustrated magazines from the beginning of the 20th century Actualidades, Novedades and Prisma. This novel literary format, associated with the modernist horizon, was cultivated not only by Peruvian male writers, but also by female writers. The main objective of this article is to vindicate the figure and work of María Augusta Arana, an author completely unknown to literary history. Her social trajectory and her briefly essays are studied. Furthermore, are analyzed the short stories “Un Lote negro” (1903), published in Novedades, and “El desenlace de un sueño” (1907), published in Actualidades, are analyzed. Due to the quality of her work, she is one of the founders of the modern short story in Peru.